Translation Analysis of the Article in National Geographic Magazine Entitled “The End of Trash” by Robert Kunzig, 2020 Edition - Awali, Dafa Maora; Larassati, Anisa (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2024)
This study aimed to identify the translation techniques and quality of the article "The End of Trash” from the 2020 edition of National Geographic Magazine. The data comprises sentences from three subchapters Food, Clothes, and Metal in both English and Indonesian. This research used a descriptive qualitative method to analyze data. The study identifies translation techniques based on Molina and Albir's (2002) theory and evaluates translation quality according to Nababan's (2012) framework. The analysis reveales 14 translation techniques, Established Equivalent (34.9%), Reduction (17.8%), Literal Translation (8.3%), Borrowing (6.9%), Amplification (6.6%), Discursive Creation (5.5%), Transposition (4.2%), Modulation (4.2%), Adaptation (3.1%), Calque (3%), Particularization (3%), Linguistic Compression (1%), Generalization and Linguistic Amplification at (0.6%). The quality assessment indicates a high level of accuracy, with 80.9% of the translations classified as accurate, 78.5% considered acceptable, and 80.1% readable. The study suggests that future research could explore other editions of National Geographic to provide a broader perspective on translation practices.